Plasma levels of direct oral anticoagulants in real life patients with atrial fibrillation: Results observed in four anticoagulation clinics. (January 2016) - Testa, Sophie; Tripodi, Armando; Legnani, Cristina; Pengo, Vittorio; Abbate, Rosanna; Dellanoce, Claudia; Carraro, Paolo; Salomone, Luisa; Paniccia, Rita; Paoletti, Oriana; Poli, Daniela; Palareti, Gualtiero; et al.
Abstract: Introduction: Direct oral anticoagulant (DOAC) intra- and inter-individual variability was previously reported, but its magnitude is still considered negligible for patient management. Objective: To evaluate inter- and intra-individual variability in real-world atrial fibrillation patients on dabigatran, rivaroxaban or apixaban in four Italian anticoagulation clinics and to assess the correlation between DOAC plasma concentration and creatinine-clearance (CrCl). Materials and Methods: A total of 330 consecutive patients were enrolled, of which 160 were on dabigatran (70 and 90 taking 150 mg or 110 mg twice-daily, respectively), 71 on rivaroxaban (37 and 34 taking 20 mg or 15 mg once-daily) and 99 on apixaban (73 and 26 taking 5 mg or 2.5 mg twice-daily). Blood was taken at trough and peak within the first month (15–25 days) of treatment. Diluted-thrombin-time (dTT) calibrated for dabigatran and anti-FXa calibrated for rivaroxaban or apixaban was performed. Results: Mean inter-individual variability expressed as overall CV values for all drugs was lower at peak (CV = 46%) than at trough (CV = 63%). Mean CV% intra-individual variability was 36.6% at trough and 34.0% at peak. Correlation with CrCl was poor for all drugs and only dabigatran at trough showed a significant correlation. Conclusion: This multicenter study confirms high DOAC inter-individual variability that cannot be explained by the rate of renal clearance to which the three DOAC were subjected since the correlation with CrCl was relatively poor. This poor correlation suggests caution in using CrCl as the sole laboratory parameter to indirectly evaluate residual circulating DOAC. Highlights: We evaluated DOAC plasma variability and their correlation with renal function. DOAC inter-intra individual variability is relatively high. Correlation between DOAC plasma levels and creatinine clearance is poor. Variability cannot be accounted for by the rate of renal clearance. Specific tests for each drug should be available in real time in clinical practice.